Analisis Pemilihan Supplier Bahan Baku Edamame Dengan Metode Fuzzy Analitycal Hierarchy Process (FAHP) Di PT XYZ - Wirawan Wijaksono Walddeon; Dira Ernawati (Jurnal Kendali Teknik dan Sains, 2023)
This study aims to analyze the selection of edamame raw material suppliers at PT XYZ using the Fuzzy Analytical Hierarchy Process (FAHP) method. This research involves the process of collecting primary and secondary data which includes identification of supplier selection criteria, collection of criteria and sub-criteria data, and collection of supplier performance data. The results showed that the relevant supplier selection criteria in the context of edamame raw materials at PT XYZ were product quality, price, supply reliability, sustainability and reputation. Based on the FAHP method, the relative weight of each criterion and sub-criteria has been calculated, which helps in evaluating potential suppliers. In addition, supplier rankings are also determined based on the resulting priority values. In conclusion, the FAHP method can be used as an effective tool in selecting raw material suppliers for edamame at PT XYZ. This method helps in reducing uncertainty and complexity in decision making, as well as providing more objective and structured results.